Chronic lower back pain: diagnosis and current principles of therapy - V. A. Golovacheva; A. I. Isaikin (Неврология, нейропсихиатрия, психосоматика)
Chronic nonspecific lower back pain (LBP) is one of the most common causes of adult disability. The chronic course of back pain is often supported by the patient's unhealthy lifestyle and the use of ineffective treatments. The combination of cognitive behavioral therapy, therapeutic exercises, gradually increased physical activity, and rational pharmacotherapy are effective in most cases of chronic non-specific LBP. In this disease, nonsteroidal anti-inflammatory drugs (NSAIDs) are the first-choice drugs that should be prescribed in a short cycle. The choice of NSAIDs is determined by the presence of concurrent diseases in the patient and by the risk of developing adverse events. The paper discusses the efficacy and safety of meloxicam in non-specific NSAIDs.